Treatment Approach of Refractory Helicobacter pylori Infection: A Comprehensive Review. (May 2021) - Cortés, Pedro; Nelson, Alfred D.; Bi, Yan; Stancampiano, Fernando F.; Murray, Loren P.; Pujalte, George G.A.; Gomez, Victoria; Harris, Dana M.
H. pylori is the most common infection in the world and is associated with gastrointestinal and extra-gastrointestinal manifestations, including peptic ulcer disease, gastrointestinal bleeding, and lymphoproliferative disorders. Despite being discovered less than half a century ago, antibiotic resistance, exacerbated by medication non-adherence and inefficacy of proton pump inhibitors, has grown substantially, explaining the rising incidence of refractory H. pylori infection. In this review, we discuss risk factors, treatment options, surveillance and follow-up, as well as emerging therapies for refractory H. pylori .